Azure AI services at scale for cloud, mobile, and Edge : using Azure cognitive services and machine learning to build apps - Raman, Anand; Hoder, Chris; Bisson, Simon; Branscombe, Mary (O'Reilly Media, Inc., 2022)
Whether you're a student planning to focus on AI or an experienced software engineer with an idea for the next viral AI app, or if you want to make a business process smarter by getting AI to do some of the work, this book's got you covered. Authors Anand Raman, Chris Hoder, Simon Bisson, and Mary Branscombe show you how to build practical intelligent applications for the cloud, mobile, browsers, and edge devices using a hands-on approach. In three sections, this book introduces you to AI-oriented architecture, provides an overview of the available tools, and provides real-world examples to guide you through this architecture.All you need to get started is a working knowledge of basic cloud concepts. Become familiar with various AI offerings and capabilities Build intelligent applications using Azure Cognitive Services Train, tune, and deploy models with Azure Machine Learning, PyTorch, and the Open Neural Network Exchange (ONNX) Learn about how companies have used Cognitive Services to solve business problems Use transfer learning to train vision, speech, and language models in minutes Discover how Microsoft scaled running Azure Cognitive Services for millions of users.